Unveiling Cybersecurity Factors in Thailand’s Metaverse Adoption - Noppadon Ratanavaraha; Chetneti Srisa-An (Migration Letters, 2023)
This research aimed to identify and evaluate the Cybersecurity Factors in Thailand’s Metaverse Adoption by adopting a mixed-method approach. The qualitative study categorized participants into four groups, which comprised 15 experts in cybersecurity and the Metaverse. Data collection involved e-Focus groups combined with digital surveys and employed Fuzzy Set Theory for data analysis. In the quantitative study, data were collected from 800 Meta users in Thailand using a digital survey and Exploratory Factor Analysis for data analysis. In the qualitative conclusion, the analysis, utilizing the Fuzzy Technique with a 0.917 threshold, identified key components. In the quantitative conclusion, the research encompassed 800 Meta users in Thailand. Exploratory Factor Analysis confirmed a variable set that accounts for 83.885% of the total variance, categorized into four key components. Additionally, eleven factors were consolidated into a unified entity called ’Cybersecurity Factors in Thailand’s Metaverse Adoption’ (CFTM).